2017
DOI: 10.1177/0146167217722557
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Innocence of Youth: Moral Sanctity Values Underlie Censorship From Young Children

Abstract: Three studies examined the relationship between people's moral values (drawing on moral foundations theory) and their willingness to censor immoral acts from children. Results revealed that diverse moral values did not predict censorship judgments. It was not the case that participants who valued loyalty and authority, respectively, sought to censor depictions of disloyal and disobedient acts. Rather, censorship intentions were predicted by a single moral value-sanctity. The more people valued sanctity, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Given the use of sex‐related items as a basis for the purity measure, one of which (homosexual sex) has become more accepted by the public over the past several decades (Schnabel and Sevell 2017), it is somewhat surprising that the effect sizes for purity were similar for laws regulating sexual and nonsexual behavior in different decades. However, the findings are consistent with research suggesting that moral concerns about the moral foundation purity drive various social policy attitudes (Koleva et al 2012), as well as research showing that moral purity concerns are associated with desires to regulate “immorality” across sexual and nonsexual domains (Anderson and Masicampo 2017). By contrast, the effects of moral absolutism and moral collectivism on support for moral regulation laws were more variable.…”
Section: Discussionsupporting
confidence: 86%
“…Given the use of sex‐related items as a basis for the purity measure, one of which (homosexual sex) has become more accepted by the public over the past several decades (Schnabel and Sevell 2017), it is somewhat surprising that the effect sizes for purity were similar for laws regulating sexual and nonsexual behavior in different decades. However, the findings are consistent with research suggesting that moral concerns about the moral foundation purity drive various social policy attitudes (Koleva et al 2012), as well as research showing that moral purity concerns are associated with desires to regulate “immorality” across sexual and nonsexual domains (Anderson and Masicampo 2017). By contrast, the effects of moral absolutism and moral collectivism on support for moral regulation laws were more variable.…”
Section: Discussionsupporting
confidence: 86%
“…Although previous research has suggested that children may have some sort of distinctive status in the moral domain (Anderson & Masicampo, 2017; Goodwin & Landy, 2014; H. M. Gray et al, 2007), these five studies are the first empirical investigation to systematically compare variables that predict moral judgments about adults and young children.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we were surprised that very few parents stated that talking about BLM was Not Appropriate for their child, given the prevalence of the preservation of (white) childhood innocence (R. A. Anderson & Masicampo, 2017) and some evidence of this reasoning among white parents from prior research (e.g., Abaied & Perry, 2021; Rogers, Niwa, et al, 2021).…”
Section: Discussionmentioning
confidence: 95%